Correlating Digestion-Driven Self-Assembly in Milk and Infant Formulas with Changes in Lipid Composition - Pham, Anna C; Peng, Kang-Yu; Salim, Malinda; Ramirez, Gisela; Hawley, Adrian; Clulow, Andrew J; Boyd, Ben J (ACS applied bio materials, 2020)
Lipids in mammalian milks such as bovine milk and human breast milk have been shown to self-assemble into various liquid crystalline materials during digestion. In this study, the direct correlation between the composition of the lipids from three types of mammalian milk, three brands of infant formulas (IFs), and soy milk and the liquid crystalline structures that form during their digestion was investigated to link the material properties to the composition. The self-assembly behavior was assessed using in vitro digestion coupled with in situ small-angle X-ray scattering (SAXS). Lipid composition was determined during in vitro digestion using ex situ liquid chromatography–mass spectrometry. All tested milks self-assembled into ordered structures during digestion, with the majority of milks displaying nonlamellar phases. Milks that released mostly long-chain fatty acids (>95 mol % of the top 10 fatty acids released) with more than 47 mol % unsaturation predominantly formed a micellar cubic phase during digestion. Other milks released relatively more medium-chain fatty acids and medium-chain monoglycerides and produced a range of ordered liquid crystalline structures including the micellar cubic phase, the hexagonal phase, and the bicontinuous cubic phase. One infant formula did not form liquid crystalline structures at all as a consequence of differences in fatty acid distributions. The self-assembly phenomenon provides a powerful discriminator between different classes of nutrition and a roadmap for the design of human milklike systems and is anticipated to have important implications for nutrient transport and the delivery of bioactives.